The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/fcsr.12411
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Antecedents of Iranian College Students’ Residential Satisfaction using Structural Equation Modeling

Abstract: By living far away from the family, college students lose social support from their families, and therefore, they may feel loneliness, and lack of attachment to the new environment. The main objective of this study was to investigate the factors affecting residential satisfaction (RS) of students living in dormitories. A survey was developed and distributed to 850 students of the dormitory of Shahid Beheshti University in Tehran, Iran. After the data had been cleaned, the statistical analyses were conducted on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Questions in their survey focused on five constructs: nature relatedness, hygiene and health services, controllability and security, social relations, and equipment and installations. Nazarpour and Norouzian‐Maleki (2021) found that social relations and nature relatedness had the greatest influence on residential satisfaction for these Iranian students.…”
Section: Discussion Of Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Questions in their survey focused on five constructs: nature relatedness, hygiene and health services, controllability and security, social relations, and equipment and installations. Nazarpour and Norouzian‐Maleki (2021) found that social relations and nature relatedness had the greatest influence on residential satisfaction for these Iranian students.…”
Section: Discussion Of Resultsmentioning
confidence: 95%
“…Nazarpour and Norouzian‐Maleki (2021) collected data from 850 students in one dormitory in Tehran, Iran. Questions in their survey focused on five constructs: nature relatedness, hygiene and health services, controllability and security, social relations, and equipment and installations.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The housing satisfaction of students is an essential theme in housing studies. However, several global studies on the housing satisfaction of students focus on on-campus accommodation (see Adewunmi et al, 2011;Amole, 2009;Najib et al, 2011;Nazarpour & Norouzian-Maleki, 2021;Oke et al, 2017;Sawyerr & Yusof, 2013;Xu et al, 2020), with only a few focusing on satisfaction in off-campus student housing (Zasina & Antczak, 2021). Yet, since it has been established that on-campus accommodation facilities are limited, offcampus housing seems to be the principal accommodation source for students (Chang, 2017;Chang, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%